AEON JUSCO – contributions towards society and environment / Norhasimah Md Razali...[et al.] - Md Razali, Norhasimah; Othman, Nur Aminah; Mohd Sanusiy, Nurul Hafizah (2010)
This article gives information about AEON CO. (M) BHD. profile which includes the company’s history, current operations and core principles. The objective of this research is to gain information about AEON Jusco social contributions towards the society and environment. In this article, we will know more about what AEON Jusco has done to contribute towards the society and environment. This article also explains about the various programs implemented by AEON Jusco that give benefits to the community.